Saberes docentes constituídos mediados pelas Tecnologias Digitais (TD) : desafios docentes de ciências e matemática em tempo de pandemia da Covid-19 - Pinto, Rafael Alberto Vital (2023)
Technology has been a transforming force in society's behavior throughout human history. Technique, which is based on science, has become a powerful form of material intervention that increasingly affects our cultural way of life and our forms of sociability. This has motivated the understanding of the knowledge required by the digital universe of contemporary society and impacted the development of educational activities mediated by Digital Technologies (DTs). Thus, this study aims to investigate the Teaching Knowledge already constituted by Science and Mathematics teachers of Basic Education at the José Ângelo dos Santos State School, located in the municipality of Barra do Garças - MT, which are mediated by Digital Technologies (DT) . In addition, analyze the difficulties faced by these professionals during emergency remote teaching due to the COVID-19 pandemic, as well as identify the alternatives adopted to overcome these difficulties. The methodology used in this research was the Case Study, having as a methodological approach the qualitative research, for that, data collection instruments were used for data production, such as interviews and interviews with the research subjects. Data analysis took place through descriptive and interpretive analyzes of the categorization of Teaching Knowledge mediated by DT, a proposal suggested by Content Analysis. The results obtained show the experiences of existing Teaching Knowledge and the difficulties and alternatives mobilized during remote teaching in times of the Covid-19 pandemic. Finally, the research highlights the importance of public policies and initial and continuing education programs that encourage and support teachers in the adoption of DTs, aiming at improving educational results and promoting education in times of crisis.